2021
DOI: 10.1155/2021/9920007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socioeconomic Determinants on the Quality of Life of Moroccan Breast Cancer Survivors Diagnosed Two Years Earlier at the National Institute of Oncology in Rabat

Abstract: Introduction. The objective of this study was to investigate the impact of socioeconomic determinants on the quality of life of Moroccan women with breast cancer two years after their diagnosis who are followed up at the National Institute of Oncology (INO) in Rabat. Methods. This is a cross-sectional study that was conducted between May 2019 and September 2020. The sample size was 304 women. Data were collected using the EORTC QLQ-C30 and EORTC QLQ-BR 23 questionnaires in the Moroccan dialect. Results. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
2
0
0
Order By: Relevance
“…Gangane et al [23] reported that the mean score across all groups for QOL was 55.5, slightly higher than the present study. Ismaili et al [24] have used other scores and they have found total health scores (mean: 57.2 ± 25.4), which are similar to the present study. In their study using the functional assessment of cancer therapy scores, Pandey et al [21] found that QOL scores in breast cancer patients in all four domains of assessment were near median scores, which are near 50% of the maximum scores.…”
Section: Discussionsupporting
confidence: 90%
“…Gangane et al [23] reported that the mean score across all groups for QOL was 55.5, slightly higher than the present study. Ismaili et al [24] have used other scores and they have found total health scores (mean: 57.2 ± 25.4), which are similar to the present study. In their study using the functional assessment of cancer therapy scores, Pandey et al [21] found that QOL scores in breast cancer patients in all four domains of assessment were near median scores, which are near 50% of the maximum scores.…”
Section: Discussionsupporting
confidence: 90%
“…As has been frequently reported in both high-and low-income countries, our study found statistically significant disparities in patient wellbeing by socioeconomic status, with patients in poor wealth categories reporting worse wellbeing compared to the richest patients [48][49][50][51][52][53]. While providing facilitated access to cancer care during COVID-19 pandemic benefited patients overall, these services were not sufficient to equalize outcomes by wealth categories.…”
Section: Discussionsupporting
confidence: 42%
“…Although the relationship between self-stigma and financial challenges has not been extensively studied in Africa, previous research shows that the cost of care is a major concern for cancer patients [ 29 , 30 ]. Other studies in sub-Saharan countries have also found that a cancer diagnosis can impact a patient’s earnings and ability to generate income for the family during treatment [ 31 , 32 ]. The financial burden of healthcare, also referred to as financial toxicity, is receiving new attention globally [ 28 ].…”
Section: Discussionmentioning
confidence: 99%